The light in the skull : an odyssey of medical discovery - Glasser, Ronald (Boston : Faber & Faber, 1997)
A study of pioneering scientists and doctors from throughout history who have challenged established beliefs about illness and disease and gone on to make discoveries that have changed the lives of billions of people.
Includes bibliographical references (p. 207-209).
Booklist.
Publisher's Weekly.
School Library Journal.
Adult
Keywords: Medicine -- History; Medicine -- History